Implementation of the Freedom to Learn Curriculum and Its Impact on the Achievement - Heatubun, Antonius; Talaud, Fransiskus (EDUTEC : Journal of Education And Technology, 2024)
This research aims to examine, analyze, and interpret the implementation of the independent learning curriculum on student achievement at SMP Sta. Theresia. The readiness of educators in implementing the independent learning curriculum based on competence, creative innovation, and work ethic is a driving factor in improving student achievement at SMP Sta. Theresia. These four aspects support effective teaching strategies and models. The research is descriptive in nature, employing a qualitative approach. Data were obtained through interviews with several informants, namely teachers at SMP Sta. Theresia who implemented the independent learning curriculum. The research results indicate that the optimization of the implementation of the independent learning curriculum significantly improves student achievement. However, challenges were also detected in the form of learning culture. The key to the success of implementing the independent learning curriculum lies in the efforts of teachers and students to change their mindset to achieve optimal results. Over the past two years at SMP Sta. Theresia Malalayang, teachers have undergone a transformation in their thinking for the success of effective education, designing strategies that prioritize competence implementation. The improvement in student achievement is evident, and the independent learning curriculum contributes to this achievement by adapting modules according to the interests and learning styles of students, enabling each student to excel. The Student Pancasila Profile Development Program, an initiative of the independent learning curriculum absent in the previous curriculum, aims to strengthen diverse competencies in building a student profile that emphasizes Pancasila values. This serves as the connecting point and supporting factor for the improvement of student achievement in the implementation of the independent learning curriculum at SMP Sta. Theresia Malalayang.